《昆兰第 4洞窝训话》：分化与阶层 4QInstruction: Divisions and Hierarchies) - Wold, Benjamin (My University, 2024)
In 4QInstruction: Divisions and Hierarchies, Benjamin Wold challenges the interpretation of 4QInstruction as a deterministic and dualistic composition. In a re-examination of key fragments he offers new reconstructions and translations that indicate 4QInstruction envisaged wisdom available to all humanity, divisions among humankind and communities as the result of individual adherence to wisdom, and a hierarchy of authority as a result of individual merit.

在《昆兰第4洞窟训诲：分化与阶层》中，Benjamin Wold 讨论了《第4洞窟训诲》中的几种不同关系，即：训导者与领悟者（第 1 章），灵与肉（第 2 章），以及妥拉 与“奥秘”（רז נהיה）（第 3 章）。综合以上三章，有助于在第二圣殿晚期犹太人智慧文学和当时智慧发展的更广泛背景下评估这部著作。本专著的一个目标是反驳一种流行的观点，即认为《第4洞窟训诲》是二元论和决定论的作品。相反，《第4洞窟训诲》认为人们具有道德主体性，他们应该寻求在创造中发现的善恶知识，这部分通过“奥秘”（רז נהיה）来表达。“奥秘”的关系通过时间的三部分划分来表达，包括从开始到结束的整个创造过程，这引发了人们对西奈山和摩西律法在《第4洞窟训诲》中的地位的质疑。最后一章转向了关于《托拉》（ Torah）在本著作中的争论，结论是《托拉》从未被主题化或提及的原因是“奥秘”（等同于“真理”）比西奈山更早出现。
PUBLISHED
Chinese University of Hong Kong
Keywords: Identities in Transformation; Inclusive Society